Structural and dielectric relaxor properties of yttrium-doped Ba(Zr0.25Ti0.75)O-3 ceramics - Badapanda, T.; Rout, S. K.; Cavalcante, L. S. [UNESP]; Sczancoski, J. C. [UNESP]; Panigrahi, S.; Sinha, T. P.; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2010)
In this work, [Ba1-xY2x/3](Zr0.25Ti0.25)O-3 ceramics with different concentrations (x = 0, 0.01, 0.025 and 0.05) were synthesized by Solid state reaction. The X-ray diffraction patterns indicated that these crystalline ceramics have a perovskite-type cubic structure. The scanning electron microscopy micrographs revealed that the addition of yttrium (Y) into the lattice is able to change the microstructure. The temperature dependent dielectric properties were investigated in the frequency range from 1 kHz to 1 MHz. The relaxor property was analyzed by the broadening of the maximum dielectric permittivity as well as its shifting to high temperatures with the variation of frequency measurements. The Curie temperature decreases with the addition of Y content into the lattice. The diffusivity and the relaxation strength were estimated using the modified Curie-Weiss law. The relaxation time of these materials was well-adjusted by the Vogel-Fulcher equation. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Sintering; Microscopy; Electrical properties